(untitled) (Palíndromo, 2025)
The article discusses the work of the Rio Art Museum (MAR) in contact with Rio de Janeiro’s port area, where the institution’s building is located. One kilometer from the museum is Valongo Wharf, which in the 18th and 19th centuries was the largest port in the world for receiving Africans for enslavement. The opening of MAR in 2013 was part of a project to revitalize the port area, one of the milestones of which was the excavation of Valongo Wharf after it had been landfilled for a century. Through an analysis of the exhibitions presented at the museum during its first decade, as well as its educational program and dialogue with the surrounding community, this article investigates how MAR’s initiatives contributed to artistic, educational, and social awareness. The conclusion is that, after a period of maturation of its institutional premises, the museum found in its integration with the local population and in the critical analysis of the history of its surroundings a way to reinforce the relevance of its existence and its programming.